Hybrid thermal performance enhancement of a circular latent heat storage system by utilizing partially filled copper foam and Cu/GO nano-additives. (15th December 2020) - Hashem Zadeh, Seyed Mohsen; Mehryan, S.A.M.; Ghalambaz, Mohammad; Ghodrat, Maryam; Young, John; Chamkha, Ali
Abstract: Low thermal response of latent heat thermal energy storage (LHTES) systems has been their main barrier in large-scale applications and commercialization. Amongst all proposed techniques, the incorporation of metal foam appears to be more promising owing to the notable thermal conductivity and high ratio of surface-area-to-volume. Nonetheless, metal foams augment the thermal response of the LHTES systems at the expense of reducing their thermal capacity and weakening natural convection. The principal aim of the present study is to numerically assess the capability of hybrid heat transfer enhancement of an LHTES through a combination of partial metal foam and nano-additives. Capric acid is considered as the phase change substance in a circular-shape thermal energy storage unit with a two-pass heat pipe. A combination of Copper foam and Cu/GO nano-additives is analyzed as the hybrid enhancement approach. The outcomes show that the combination of partial copper foam with Cu/GO nano-additives is more effective than each enhancement technique separately. Moreover, the results reveal that the charging power of the LHTES can be enhanced to about four times higher than the case of pure PCM at the cost of only a 3% reduction of the thermal storage's capacity.